Investigation on heat and mass transfer in hygroscopic random charged fiber webs - Zhu, Q. Y. (2013)
Hygroscopic charged fiber webs include a large number of interconnected capillaries formed by randomly distributed pores. The simultaneous heat and mass transfer in hygroscopic charged fiber webs is different from traditional flows in macro-channels resulted from the electrokinetic phenomena in micro-channels. In this paper, a mathematical model is presented with consideration of a quintic polynomial pore size distribution evaluated from a series of experiments and the electrokinetic phenomena resulting in a higher flow friction. The liquid diffusion coefficient in this model can be expressed as View the MathML source. With specification of initial and boundary conditions, the governing equations are solved numerically and distributions of the temperature, the moisture concentration, and liquid water content in hygroscopic fiber webs are obtained. The comparison with the experimental measurements shows the rationality of this model in simulating the coupled heat and mass transfer in hygroscopic charged fiber webs with consideration of the electrokinetic phenomena.